2016
DOI: 10.1016/j.livsci.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

How heat stress (continuous or cyclical) interferes with nutrient digestibility, energy and nitrogen balances and performance in broilers

Abstract: The effect of continuous and cyclical heat stress on broiler growth performance, nutrient digestibility, energy and nitrogen balances was investigated. Four hundred and fifty, 21-day-old, Cobb male broilers were raised in battery cages in five treatments: 22C/AL (continuous 22°C, ad libitum feed consumption); 32C/AL (continuous 32°C, ad libitum feed consumption); 22C/PF32C (continuous 22°C, pair-fed on the daily feed intake of 32C/AL); CY/AL (cyclical-32°C for 8 h and 25°C for 12 h, ad libitum feed consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 30 publications
6
41
0
3
Order By: Relevance
“…Broilers exposed to continuous heat stress increased ME intake (20.3%) and heat production (35.5%), and decreased ME retention (20.9%), ME efficiency (32.4%), nitrogen intake, nitrogen retention (50.4%) and nitrogen efficiency (33.1%) compared to controls. This indicates that a continuous HS had a stronger adverse effect than cyclical ones, which has a less effect on performance and digestibility of nutrients (Souza et al 2016).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Broilers exposed to continuous heat stress increased ME intake (20.3%) and heat production (35.5%), and decreased ME retention (20.9%), ME efficiency (32.4%), nitrogen intake, nitrogen retention (50.4%) and nitrogen efficiency (33.1%) compared to controls. This indicates that a continuous HS had a stronger adverse effect than cyclical ones, which has a less effect on performance and digestibility of nutrients (Souza et al 2016).…”
Section: Introductionmentioning
confidence: 91%
“…Nonetheless, the influence of HS in the utilisation of ME still requires further verification, as different authors have found an elevation (Keshavarz and Fuller 1980), a decline (Yamazaki and Zi-Yi 1982;Souza et al 2016;Attia and Hassan 2017) and no influence (Geraert et al 1992;Faria Filho et al 2007). Additionally, HS influences meat yield, carcase composition, and ME, independently of feed intake (Cahaner et al 1995;Geraert et al 1996;Attia and Hassan 2017).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations